HUBUNGAN TIPE KEPRIBADIAN HIPPOCRATES-GALENUS DENGAN TINGKAT KESABARAN MAHASISWA DALAM SISTEM KULIAH ONLINE - Nurul Dewiyana Azizah (Jurnal Perspektif, 2021)
This study aims to determine the correlation of the Hippocrates-Galenus personality type to the level of patience of students of the 2017 Sufism and Psychotherapy Department students of UIN Sunan Gunung Djati Bandung in attending online lectures. This type of research is correlational research. The study population was 90 students of the 2017 Sufism and Psychotherapy Department students of UIN Sunan Gunung Djati Bandung by using total sampling methods. Data were collected by using Hippocrates-Galenus personality profile test and patient level questionnaire in online lectures. Data were analyzed by using the Pearson C correlation technique (Contingency Coefficient). The results showed that there was no significant correlation between the Hippocrates-Galenus personality type and the level of patience of the 2017 Sufism and Psychotherapy Department students of UIN Sunan Gunung Djati Bandung in attending online lectures (p = 0,157). It is hoped that further researchers can conduct research with other methods in order to obtain more comprehensive results.